Coping with resettlement: A livelihood adaptation analysis in the Mekong River basin - Kuraa, Y.; Joffre, Olivier M.; Laplante, Benoit; Sengvilaykham, Bounthong (Elsevier, 2017)
tA major driver of change in the Mekong River basin relates to hydropower development and the conse-quent changes in landscape and natural resource access regime that it induces. In this paper, we examinehow the livelihoods of resettlers evolve following resettlement, and examine the determinants of thatprocess. The study takes place in the context of the Theun Hinboun Expansion Project in Lao PDR. Basedon longitudinal household surveys conducted before resettlement as well as 1, 2, and 3 years after reset-tlement, we identify the process of livelihood adaptation in resettled communities. Results show varyingcapacity to absorb shocks and cope with change even within a small village with seemingly equal con-ditions. Our results suggest that a more detailed understanding of this adaptation process is key toimproving interventions for rebuilding the livelihoods of those resettled by development projects inrural areas.